1996
DOI: 10.1103/physreva.54.2464
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous emission from an atom in a nonideal cavity: Application of a generalized master equation

Abstract: Spontaneous emission from an atom in a nonindeal cavity: Application of a generalized master equation van der Plank, R.W.F.; Suttorp, L.G. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
3
4
0
Order By: Relevance
“…The "generalized" master equation that arises by accounting for these enhanced losses has been established recently [3]. In applying this equation to the time evolution of a decaying atom in a cavity we have found that the effects of increased losses can be quite substantial [4]. These findings are in agreement with the predictions that follow from the solution of delay differential equations for the probability amplitudes [5].…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…The "generalized" master equation that arises by accounting for these enhanced losses has been established recently [3]. In applying this equation to the time evolution of a decaying atom in a cavity we have found that the effects of increased losses can be quite substantial [4]. These findings are in agreement with the predictions that follow from the solution of delay differential equations for the probability amplitudes [5].…”
Section: Introductionsupporting
confidence: 81%
“…These findings are in agreement with the predictions that follow from the solution of delay differential equations for the probability amplitudes [5]. It may be remarked here that the effects of enhanced losses in cavities with a thin-slab geometry and with infinite mirrors, as treated in [6], are rather different from those discussed in [4,5] . In fact, in the slab configuraa e-mail: suttorp@phys.uva.nl tion the atom-field system is always in the weak-coupling regime, so that Fermi's golden rule can be used.…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations